Mild Hypothermia Attenuates Intercellular Adhesion Molecule-1 Induction via Activation of Extracellular Signal-Regulated Kinase-1/2 in a Focal Cerebral Ischemia Model - Jung Sook Choi; Jaechan Park; Kyoungho Suk; Cheil Moon; Yong-Ki Park; Hyung Soo Han (Stroke Research and Treatment)
Intercellular adhesion molecule-1 (ICAM-1) in cerebral vascular endothelium induced by ischemic insult triggers leukocyte infiltration and inflammatory reaction. We investigated the mechanism of hypothermic suppression of ICAM-1 in a model of focal cerebral ischemia. Rats underwent 2 hours of middle cerebral artery occlusion and were kept at 37°C or 33°C during occlusion and rewarmed to normal temperature immediately after reperfusion. Under hypothermic condition, robust activation of extracellular signal-regulated kinase-1/2 (ERK1/2) was observed in vascular endothelium of ischemic brain. Hypothermic suppression of ICAM-1 was reversed by ERK1/2 inhibition. Phosphorylation of signal transducer and activator of transcription 3 (STAT3) in ischemic vessel was attenuated by hypothermia. STAT3 inhibitor suppressed ICAM-1 production induced by stroke. ERK1/2 inhibition enhanced phosphorylation and DNA binding activity of STAT3 in hypothermic condition. In this study, we demonstrated that hypothermic suppression of ICAM-1 induction is mediated by enhanced ERK1/2 activation and subsequent attenuation of STAT3 action.